PENGARUH SLACK RESOURCES, UKURAN PERUSAHAAN, KEPEMILIKAN PUBLIK DAN KINERJA LINGKUNGAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILTY (CSR) PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016 – 2019 - Hasan Badilah N; Maslichah Maslichah; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to determine the effect of Slack Resources, Company Size, Public Ownership, and Environmental Performance on Disclosure of Corporate Social Responsibility at LQ45 Companies listed on the Indonesia Stock Exchange in 2016 - 2019. Based on the number of calculations, 25 companies were selected as samples. The results of the analysis use multiple linear regression analysis which shows that Slack Resources, Company Size, Public Ownership, and Environmental Performance have a significant influence on Corporate Social Responsibility simultaneously. Partially the test results show Slack Resources, Company Size, Public Ownership, and Environmental Performance have a significant effect.Keywords: Slack Resources, Company Size, Public Ownership, Environmental Performance, Corporate Social Responsibility.